Microwave Radiothermometry in Evaluating Brain Temperature Changes (Review) - O. A. Shevelev; M. V. Petrova; M. Yu. Yuriev; V. T. Dolgikh; E. M. Mengistu; M. A. Zhdanova; I. Z. Kostenkova (Общая реаниматология, 2023)
Aim. This review aims to inform physicians of different specialties (anesthesiologists, intensivists, neurologists, neurosurgeons, oncologists) about the diagnostic capabilities of microwave radiothermometry, which enables to identify and analyze features of alterations of cerebral temperature in brain damage.The review displays a critical analysis of 80 recent Russian and foreign open access publications found by keywords.The review presents major clinical features and pathophysiological mechanisms of cerebral thermal balance disruptions in brain lesions. Slow responsiveness and vulnerability of cerebral thermal homeostasis regulation mechanisms that underlie development of different temperature heterogeneity levels in the cerebral cortex in healthy brain and brain lesions are highlighted. The authors postulate their concept about the critical role of hyperthermia in the pathogenesis of brain damage and disruption of interconnections in the global central regulation system. A body of evidence explaining direct association between the depth of consciousness impairment and degree of cerebral cortex temperature heterogeneity manifestation is presented. It is emphasized that a significant increase in temperature heterogeneity with areas of focal hyperthermia accompanies an acute period of ischemic stroke, while in post-comatose state usually associated with prolonged impairment of consciousness, the temperature heterogeneity significantly subsides. It has been suggested that lowering of an increased and rising of the reduced temperature heterogeneity, for example by using temperature exposure, can improve altered level of consciousness in patients with brain damage. The diagnostic capabilities of various technologies used for cerebral temperature measurement, including microwave radiothermometry (MWR), are evaluated. Data on high accuracy of MWR in measurement of the cerebral cortex temperature in comparison with invasive methods are presented.Conclusion. In healthy individuals MWR revealed a distinct daily rhythmic changes of the cerebral cortex temperature, and badly violated circadian rhythms in patients with brain lesions. Since MWR is an easy-toperform, non-invasive and objective diagnostic tool, it is feasible to use this technology to detect latent cerebral hyperthermia and assess the level of temperature heterogeneity disruption, as well as to study the circadian rhythm of temperature changes.